Literatur review trasparansi dan akuntabilitas di Indonesia selama satu dekade: Studi bibliometric - Dewi, Silvia; Widarto, Wahyu (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This research aims to look at the implementation of transparency and accountability in Indonesia for a decade. The research method used is bibliometrics using the VOSViewer tool. Through an inclusion and exclusion process, this research examined 114 articles indexed in Scopus in the period 2013-2023. The research results show that the variables that have been frequently studied over the past ten years are related to transparency and accountability that is participation, good governance, and corruption. Transparency and accountability are principles in realizing good governance and open government. Public participation is a means of reviewing and monitoring government performance in preventing corruption. This research shows that the topic of transparency and accountability always develops every year so it will be interesting to research.